2011
DOI: 10.1177/175045891102100505
|View full text |Cite
|
Sign up to set email alerts
|

Colour Coding Scrubs as a Means of Improving Perioperative Communication

Abstract: Effective communication within the operating department is essential for achieving patient safety. A large part of the perioperative communication is non-verbal. One type of non-verbal communication is 'object communication', the most common form of which is clothing. The colour coding of clothing such as scrubs has the potential to optimise perioperative communication with the patients and between the staff. A colour contains a coded message, and is a visual cue for an immediate identification of personnel. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In this study, the PAs wore the same colour scrubs as radiographers and doctors, which may have contributed to patient confusion. Previous studies have demonstrated that nonverbal signals, such as uniform scrub colours, can influence communication and perception among patients and staff [ 46 ]. Further studies looking at the process of communication such as de Haes and Bensing [ 47 ] and Taylor, Halter and Drennan's study [ 42 ] would be beneficial to identify specific areas of possible communication breakdown between the PA and patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the PAs wore the same colour scrubs as radiographers and doctors, which may have contributed to patient confusion. Previous studies have demonstrated that nonverbal signals, such as uniform scrub colours, can influence communication and perception among patients and staff [ 46 ]. Further studies looking at the process of communication such as de Haes and Bensing [ 47 ] and Taylor, Halter and Drennan's study [ 42 ] would be beneficial to identify specific areas of possible communication breakdown between the PA and patient.…”
Section: Discussionmentioning
confidence: 99%
“…Color codes are ubiquitous in the hospital environment. They have been shown to have a beneficial effect on the safe prescription of medication, 14 adherence to patient isolation protocols, 15 safe administration of intravenous fluids, 16 avoidance of incorrect blood sampling, 17 identification of staff groups, 18 flagging patient alerts using wristbands, 19 resuscitation protocols, 20 and patient flow 21 . The result of their success is that we rely heavily on color codes at the expense of other forms of identification.…”
Section: Clinical Color Codes and Color Deficiencymentioning
confidence: 99%
“…Physician gaze, body posture, hand movements, tone of voice, facial expression and even scrub colour impact how patients perceive their clinical care and the quality of physician’s communication. 14–18 The interaction between verbal and non-verbal communication is so important to the patient–physician exchange, that many medical educators argue for explicitly training clinicians in this skillset. 19 In healthcare teams, particularly surgery, non-verbal communication enables teams to effectively operate during complex or urgent moments in the surgical encounter.…”
Section: Introductionmentioning
confidence: 99%